Respuesta :

Answer: [tex]x_1=1.63\\x_2=-2.13[/tex]

Step-by-step explanation:

1. The quadratic formula is shown below:

[tex]x=\frac{-b+/-\sqrt{b^{2}-4ac}}{2a}[/tex]

2. Given the quadratic equation given in the problem, you have that:

[tex]a=-2\\b=-1\\c=7[/tex]

3. Therefore, when you substitute the values shown above, you obtain the following result:

[tex]x=\frac{-(-1)+/-\sqrt{(-1)^{2}-4(-2)(7)}}{2(-2)}[/tex]

[tex]x_1=1.63\\x_2=-2.13[/tex]

Answer:

x =    1.637   or x = -2.137

Step-by-step explanation:

Given equation is:

-2x²-x+7 = 0

ax²+bx+c = 0 is general quadratic equation.

x = (-b±√b²-4ac) / 2a is quadratic equation to solve the quadratic equations.

Comparing general equation with given equation , we have

a = -2 , b = -1  and c= 7

Putting the given values in quadratic formula, we have

x = (-(-1)±√(-1)²-4(-2)(7) ) / 2(-2)

x = (1±√1+56) / (-4)

x = (1±√57) / (-4)

x = (1±7.549) / (-4)

x = 1-7.549 / (-4)   or x = (1+7.549) / (-4)

x = -6.549 / -4  or 8.549 / (-4)

x =    1.637        or x = -2.137 is the solution.